Does the Level of Religiosity Determine Budgetary Slacks Behavior as the Result of Superrior Pressure - Made Aristia Prayudi; Nyoman Ari Surya Dharmawan (Journal of Economics, Business, and Government Challenges, 2018)
This study aimed to investigate budgetary slack behavior due to obedience pressure to authority in governmental organization. This study also evaluates the role of religiosity in determining budgetary slack creation in such situation. The results of experiment with 64 undergraduate students as participants indicate that majority of participants obeyed the order of their immediate superior to create budgetary slack in violation of organization policy. This study also found that participants’ level of religiosity do have impact on their actual behavior to create budgetary slack. Participants with high level of religiosity are documented to create smaller amount of budgetary slack than those who have low level of religiosity when faced with obedience pressure from their superior.